Modeling of Nonlinear Interference in the Same- Wavelength Bidirectional Coherent Fiber Communication Systems - Yuan Li; Chengcheng Wu; Peili He; Wei Li; Shaohua Yu; Ming Luo; Zhongshuai Feng; Muyang Mei; Qianggao Hu; Liyan Huang; Haitao Li (IEEE Photonics Journal)
A detailed theoretical study is conducted on the nonlinear interference in the same-wavelength bidirectional coherent optical fiber communication systems. The Gaussian noise (GN) model used to evaluate nonlinear interference (NLI) in unidirectional systems is applied and extended to bidirectional transmission scenarios. The extended NLI model shows that in a bidirectional transmission communication system, the backward signal almost does not introduce additional nonlinear crosstalk to the forward signal due to the strong walk-off effect between forward and backward transmitted signals. Specifically, the ratio of the nonlinear crosstalk introduced by the forward and backward signals is about 21 dB, which means that the traditional GN model is also applicable in the bidirectional scenario. This conclusion is validated on the platform of a same-wavelength bidirectional coherent optical communication system based on Optisystem software.